Molecular Dereplication and In Vitro and In Silico Pharmacological Evaluation of Coriandrum sativum against Neuroblastoma Cells - Marcucci, Maria Cristina [UNESP]; Oliveira, Carlos Rocha; Spindola, Daniel; Antunes, Alyne A.; Santana, Leila Y K; Cavalaro, Victor; Costa, Isabelle B.; Carvalho, Ana C. de; Veiga, Thiago A M; Medeiros, Livia S.; Zamarioli, Lucas dos Santos; Gonçalves, Carolina P.; et al. (MDPI, 2022)
The aim of this study was to investigate the cytotoxic activity of the Coriandrum sativum (C. sativum) ethanolic extract (CSEE) in neuroblastoma cells, chemically characterize the compounds present in the CSEE, and predict the molecular interactions and properties of ADME. Thus, after obtaining the CSEE and performing its chemical characterization through dereplication methods using UPLC/DAD-ESI/HRMS/MS, PM6 methods and the SwissADME drug design platform were used in order to predict molecular interactions and ADME properties. The CSEE was tested for 24 h in neuroblastoma cells to the establishment of the IC50 dose. Then, the cell death was evaluated, using annexin-PI, as well as the activity of the effector caspase 3, and the protein and mRNA levels of Bax and Bcl-2 were analyzed by ELISA and RT-PCR, respectively. By UHPLC/DAD/HRMS-MS/MS analysis, the CSEE showed a high content of isocoumarins-dihydrocoriandrin, coriandrin, and coriandrones A and B, as well as nitrogenated compounds (adenine, adenosine, and tryptophan). Flavonoids (apigenin, hyperoside, and rutin), phospholipids (PAF C-16 and LysoPC (16:0)), and acylglicerol were also identified in lower amount as important compounds with antioxidant activity. The in silico approach results showed that the compounds 1 to 6, which are found mostly in the C. sativum extract, obey the Five Rules of Lipinski, suggesting a good pharmacokinetic activity of these compounds when administered orally. The IC50 dose of CSEE (20 µg/mL) inhibited cell proliferation and promoted cell death by the accumulation of cleaved caspase-3 and the externalization of phosphatidylserine. Furthermore, CSEE decreased Bcl-2 and increased Bax, both protein and mRNA levels, suggesting an apoptotic mechanism. CSEE presents cytotoxic effects, promoting cell death. In addition to the promising results predicted through the in silico approach for all compounds, the compound 6 showed the best results in relation to stability due to its GAP value.
Keywords: apoptosis; cell death; Coriandrum sativum; isocoumarins; neuroblastoma